Fabrication and Properties of Modified Poly(butylene terephthalate) with Two‐Step Chain Extension. Issue 3 (15th January 2021) - Li, Xun; Xia, Min; Qiu, Di; Long, Ren; Huang, Zihan; Li, Jie; Long, Shijun; Li, Xuefeng
Abstract: High‐viscosity, low‐crosslinked poly(butylene terephthalate) (PBT) from organic chain extenders and inorganic particles are prepared. PBT modification adopted from multifunctional, commercially available chain extension containing nine epoxy groups (ADR9) occurs in the first‐step chain extension; hydroxyl addition modified dioxazoline (BOZ) serves as the second step. Anion stratiform inorganic hydrotalcite (HT) is used to adjust the crystallization behavior and damp‐heat aging properties of PBT. The reaction between the chain extender and PBT end‐groups such as carboxyl (–COOH) and hydroxyl (–OH) enhances the interfacial bonding between the PBT matrix and dispersed HT phases. With a fraction of chain extenders in the PBT matrix, the chain‐extended PBT exhibits higher mechanical properties, intrinsic viscosity, average molecular weight, and melt viscosity than those of unmodified PBT. Damp‐heat aging resistance measurements show correlation with initial carboxyl content in the resin. Reducing the concentration of carboxyl end‐groups in the resin is shown to increase hydrolytic stability. The modified PBT resin can be used in optical fiber communication cable industry for its high level of damp‐heat aging resistance as well as good mechanic properties. Abstract : Incorporation of ADR9 and BOZ into the polymer chains of poly(butylene terephthalate) (PBT) formed stable crosslinking, utilizing a two‐step chain extension process. Compared with neat PBT, the mechanical properties of two‐step chain extension products are enhanced. The fracture behavior changed from brittle fracture to ductile fracture, and the results show that the two‐step synergistic chain extension has more advantages.